Comparative study between physical file part-21 STEP-NC and G&M code ISO6983 - Mohd Faisal, Hushim; Yusri, Yusof; N.Z. Zamri Tan; Y., Yusof (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th June 2009 at Batu Feringhi, Penang, Malaysia.